Effect of the extracellular environment on astrocyte phenotype - Smith, Z H (2020)
Astrocytes are a functionally and morphologically heterogeneous glial subtype essential for the development, function and survival of neurons in the healthy brain. Neuron-glial communication is therefore essential to normal brain function, but the mechanisms regulating signalling and anatomical association between these two cell types are still under investigation. The objective of this project was to develop in vitro models, validate the use of 3D culture techniques such as hydrogels and establish their potential for enabling astrocyte and neuron co-culture, and determine the possibility of combining 3D cell culture techniques with compartmentalized microfluidics devices. An additional aim was to discover the feasibility of replacing primary tissue with induced human astrocytes derived from fibroblasts.